Disaster Preparedness Assessment Tools of Structural Performance for Indonesian School Buildings - Wimala, Mia; Irawan, Joshua; Perceka, Wisena (International Journal of Integrated Engineering, 2022)
So far, it has been recorded that the earthquake in Indonesia has damaged many public facilities and claimed many victims. Most cases of casualties were not caused directly by the earthquake, but the result of falling debris that could not properly respond to earthquake vibrations. To avoid similar incidents in the future, all buildings in Indonesia need to be inspected and confirmed that they are safe from the threat of an earthquake, including school buildings. The absence of a specific assessment tool for earthquake-resistant school buildings underlies this research. The assessment tool was developed based on the results of a literature review of several building inspection standards in various countries due to the absence of it in Indonesia. Several research variables that were successfully identified were then validated and processed using the Analytical Hierarchy Process method. Some experts in related fields were involved in the process to formulate the significant variables, and the respective weights and scoring systems. This research produced a preliminary assessment tool consisting of two parts. The first part, which emphasizes examination by visual method, is translated into four new categories: Building Slope Inspection, Sub-structure Component Inspection, Upper Structure Component Inspection, and Document Inspection, with 12 sub-categories and 28 indicators. Meanwhile, the second part emphasizes non-destructive testing as an additional score (in percentage) in the assessment of structural components preparedness. It includes three types of tests for concrete and two tests for steel materials. The level of preparedness for the structural components of a good school building needs to meet a minimum score of 70%. National Disaster Management Agency (National Disaster Management Agency - BNPB)